1998
DOI: 10.1172/jci1020
|View full text |Cite
|
Sign up to set email alerts
|

MIP-1alpha as a critical macrophage chemoattractant in murine wound repair.

Abstract: At sites of injury, macrophages secrete growth factors and proteins that promote tissue repair. While this central role of the macrophage has been well studied, the specific stimuli that recruit macrophages into sites of injury are not well understood. This study examines the role of macrophage inflammatory protein 1 ␣ (MIP-1 ␣ ), a C-C chemokine with monocyte chemoattractant capability, in excisional wound repair. Both MIP-1 ␣ mRNA and protein were detectable in murine wounds from 12 h through 5 d after injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
178
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(194 citation statements)
references
References 28 publications
12
178
0
4
Order By: Relevance
“…This suggests that MCP-1 predominantly acts by inducing migration during endothelial wound injury. Our results expand findings that MCP-1 and MIP-1␣ are critical in wound repair by mediating macrophage recruitment 43,44 and that MCP-1 may facilitate angiogenesis, 23 implying that these processes are in part due to endothelial mechanisms.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that MCP-1 predominantly acts by inducing migration during endothelial wound injury. Our results expand findings that MCP-1 and MIP-1␣ are critical in wound repair by mediating macrophage recruitment 43,44 and that MCP-1 may facilitate angiogenesis, 23 implying that these processes are in part due to endothelial mechanisms.…”
Section: Discussionsupporting
confidence: 83%
“…Murine skin wound healing models have demonstrated that CCL2, CCL3, and CCL5 also play critical roles in macrophage recruitment. [50][51][52][53][54] Macrophages are essential for normal wound repair providing a source of cytokines, growth factors, and chemokines. 44,50,55 Once recruited, the wound microenvironment strongly influences phenotypic polarization of macrophages enabling functional heterogeneity through differential chemokine, cytokine, and receptor repertoires (Fig.…”
Section: Inflammatory Phasementioning
confidence: 99%
“…Immediately before analysis, tissues were homogenized and sonicated in an antiprotease buffer (Roche, Laval, Canada) as previously described (21)(22)(23)(24). Homogenates were centrifuged to remove debris and were then passed through 1.2-m pore size filters (Gelman Sciences, Ann Arbor, MI).…”
Section: Assay Of Chemokine Protein Content In Tissuesmentioning
confidence: 99%